Contribution of Immunoglobulin Enhancers to B Cell Nuclear Organization - Bruzeau, Charlotte; Cook-Moreau, Jeanne; Pinaud, Eric; Le Noir, Sandrine (Frontiers in Immunology, 2022)
B cells undergo genetic rearrangements at immunoglobulin gene (Ig) loci during B cell maturation. First V(D)J recombination occurs at early B cell stages and then class switch recombination (CSR) and somatic hypermutation (SHM) occur during mature B cell stages. Given that RAG1/2 induces DNA double strand breaks (DSBs) during V(D)J recombination and AID leads to DNA modifications (mutations during SHM or DNA DSBs during CSR), it is mandatory that IgH rearrangements have to be tightly regulated to avoid any mutations or translocations within oncogenes. Ig loci contain various cis-regulatory elements that are involved in germline transcription, chromatin modifications or RAG/AID recruitment. Increasingly, Ig cis-regulatory elements are recognized as being involved in nuclear positioning, heterochromatin addressing and chromosome loop regulation. In this review, we examined multiple data showing the critical interest of studying Ig gene regulation at the whole nucleus scale. In this context, we highlighted the essential function of Ig gene regulatory elements that now have to be considered as nuclear organizers of B lymphocytes.